Complete Remission in Paralytic Late Tick-Borne Neurological Disease Comprising Mixed Involvement of Borrelia, Babesia, Anaplasma, and Bartonella: Use of Long-Term Treatments with Antibiotics and Antiparasitics in a Series of 10 Cases - Paul Trouillas; Michel Franck (MDPI AG, 2023)
This study aimed to demonstrate that severe neurological motor deficits in the context of late tick-borne disease with mixed microorganism involvement are eligible for long-term combined antibiotic/antiparasitic treatments. The inclusion criteria were: 1. neurological limb paralysis with a disability score >4 according to the EDSS Kurtzke disability scale; 2. serological tests pointing to an involvement of the main tick-borne microorganisms Borrelia burgdorferi s.l., Babesia, Anaplasma, and Bartonella; 3. a general disease for more than 6 months with fatigue, pain and subjective cognitive deficit. The patients were administered long-term treatments with repeated cycles (at least three) of 35-day IV ceftriaxone and repeated oral regimens of azithromycin-doxycycline and azithromycin-doxycycline-rifampicin. For Babesia, repeated courses of atovaquone-azithromycin were administered. Ten patients had intractable or severe motor deficits before treatment in the context of Borrelia (two cases) Borrelia-Babesia (four cases), Borrelia-Babesia-Anaplasma (two cases), Borrelia-Babesia-Anaplasma-Bartonella (one case) and Babesia-Anaplasma (one case). For several months, five had been in wheelchairs, and four had been walking with sticks. Seven patients out of 10 (70%) showed complete remission after a mean active treatment duration of 20.1 + 6.6 months, with a mean number of 4 ceftriaxone cycles. Three patients showed an initial remission but suffered secondary antibiotic/antiparasitic-resistant motor recurrences. Among the nine patients with Borrelia serologic positivity, treatments obtained complete remission in seven cases (77%). The findings of this ten-case series suggest the usefulness of long-term antibiotic/antiparasitic treatments in patients with severe late tick-borne neurological deficits with highly significant elements of tick-borne involvement.